Hukum Bisnis Sulam Bedak (Beauty Balm Face Glow) Perspektif Anggota Komisi Fatwa MUI Kota Medan - Ilmi Aulia Ismail; Imam Yazid (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Powder embroidery or Beauty Balm (BB) Face Glow is a beauty trend that is increasingly popular in the cosmetics industry. This procedure is carried out by implanting color pigments into the outermost layer of skin using a microneedling technique, resulting in bright and smooth looking skin without the need for daily makeup application. However, from the perspective of Islamic law, this practice is still controversial. This research aims to analyze the law of powder embroidery based on the views of members of the Medan City MUI Fatwa Commission using descriptive-analytical qualitative methods. The results of the research show that powder embroidery is categorized as haram because it resembles tattoos and is included in the practice of changing Allah's creation (QS. An-Nisa: 119). Even though it does not block the ablution water and does not invalidate the prayer, this practice is still prohibited if it is only for aesthetic purposes. From a business aspect, powder embroidery services are also considered impermissible in Islam because they support practices that are contrary to sharia. The clerics emphasized the importance of seeking halal sustenance and appealed to Muslim women to decorate in permitted ways, such as using halal cosmetics that are not permanent.